Inclusive growth in Sub-Saharan Africa: Exploring the interaction between ICT diffusion and financial development - Isaac K. Ofori; Dennis B. Osei; Imhotep P. Alagidede (Telecommunications Policy, 2022)
Despite the momentous rise in ICT diffusion, and financial development in sub-Saharan Africa (SSA), their plausible joint effect on inclusive growth have not been explored, leaving a lacuna in the literature. This study, therefore, examines the direct and indirect effects of ICT diffusion on inclusive growth in 42 SSA countries over the period 1980-2019. We provide evidence robust to several specifications from the dynamic system GMM to show that: (i) ICT skills, access and usage induce inclusive growth in SSA, and (ii) the effects of ICT skills, access and usage are enhanced in the presence of financial development. These findings remain the same when we focussed on financial institution access. Policy recommendations are provided in line with the region's green growth agenda and striving efforts at improving socioeconomic development.
Keywords: D63; E5; G2; I3; L96; O11; O55; 330; ICT Diffusion; Inequality; Financial Development; Financial Inclusion; Inclusive Growth; Poverty; Sub-Saharan Africa